Industrial training report: Pertubuhan Keselamatan Sosial (Dungun) Pejabat Perkeso Dungun / Nur Hanani Rusli - Rusli, Nur Hanani (Perpustakaan Tengku Anis, 2017)
The industrial training report based on the period from 1st February 2017 until 3dh June 2017 in Unit Pentadbiran & Kewangan, Unit Faedah and Unit Penguatkuasaan at Pertubuhan Keselamatan Sosial (PERKESO) Dungun branch. In this industrial training report the student will be discussing regarding the period starting with the organization introductory followed with department introduction along business tasks. In this report, it was highlighted about the training activities, experience skills and challenges that the student has been encountered. All training activities and special project are recorded in this industrial training report. The student has been involved in creating corporate branding which demanding the ability of the student to create powerful and impactful corporate branding.